2022
DOI: 10.1007/s12033-022-00582-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study to Unleash the Putative Inhibitors of Serotype2 of Dengue Virus: Insights from an In Silico Structure-Based Drug Discovery

Abstract: Dengue fever is a mosquito-borne disease that claims the lives of millions of people around the world. A number of factors like disease’s non-specific symptoms, increased viral mutation, growing antiviral drug resistance due to reduced susceptibility, unavailability of an effective vaccine for dengue, weak immunity against the virus, and many more are involved. Dengue belongs to the Flaviviridae family of viruses. The two species of the vector transmitting dengue are Aedes aegypti and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…In addition, its methanol extract also exerts broad-spectrum antibacterial activity [ 12 ], as well as antioxidant, antiplasmodial, and anticancer properties (this study). Computational docking tools are used by researchers all around the world to uncover and evaluate the binding affinity of compounds that fit a protein’s binding site [ 19 ]. From the above in vitro and in vivo evidence, four protein models were chosen as molecular docking targets, as they were previously crystallized and/or used for in silico studies to investigate the binding affinity of particular compounds: 3EUB as an antioxidant target protein [ 77 ], 3VSL as an antibacterial target protein [ 78 ], 3QS1 as an antiplasmodial target protein [ 79 ], and 3GD4 as an anticancer target protein [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, its methanol extract also exerts broad-spectrum antibacterial activity [ 12 ], as well as antioxidant, antiplasmodial, and anticancer properties (this study). Computational docking tools are used by researchers all around the world to uncover and evaluate the binding affinity of compounds that fit a protein’s binding site [ 19 ]. From the above in vitro and in vivo evidence, four protein models were chosen as molecular docking targets, as they were previously crystallized and/or used for in silico studies to investigate the binding affinity of particular compounds: 3EUB as an antioxidant target protein [ 77 ], 3VSL as an antibacterial target protein [ 78 ], 3QS1 as an antiplasmodial target protein [ 79 ], and 3GD4 as an anticancer target protein [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, bioinformatics tools aid drug discovery by using all primary data gathered from in vivo and in vitro studies in a short time and at a lower cost. In silico molecular docking is one of the most effective ways to find novel ligands for proteins with known structures, thus playing an essential role in structure-based drug development [ 19 ]. A preliminary study (GC–MS) showed that the stem extract of B. cernua contained more compounds than the leaf extract.…”
Section: Introductionmentioning
confidence: 99%
“…25 The adaptability of the dengue virus, characterized by the presence of four unique serotypes, poses significant challenges to control. 26,27 This is because patients who have previously recovered from one serotype remain vulnerable to infection by the other serotypes, which may result in more severe manifestations of the disease during subsequent outbreaks. 28,29 Furthermore, the low or unavailability of healthcare support in numerous places hampers timely identification and treatment that exacerbates the impact of dengue outbreaks.…”
Section: Possible Reasons Behind the Frequent Dengue Outbreaksmentioning
confidence: 99%
“…The degree of fluctuation in RMSD is inversely proportional to the stability of a complex-the lesser the variation, the greater the stability. [52,53] All trajectories were significantly equilibrated throughout the simulation phase. Figure 11 shows the RMSD of synthesized compound 4a and standard SB203580, and it was observed that the complex was stable for the simulation period.…”
Section: Glide Energymentioning
confidence: 99%